Back to basics – ECG impedance analysis for CPR quality control and feedback after out-of-hospital cardiac arrest: a pilot study. (26th December 2010) - Lyon, Richard
Abstract : Background: Out-of-hospital cardiac arrest (OHCA) remains a leading cause of mortality. Survival from OHCA depends on good quality cardiopulmonary resuscitation from ambulance personnel. The 'time on the chest' and interruption time for defibrillation have recently been shown to be pivotal to survival. Electrocardiograph impedance analysis software allows retrospective quality control and feedback to ambulance crews after a resuscitation attempt. Telemetry and analysis of prehospital resuscitation episodes has not yet been employed in the UK. Aims: To establish the feasibility of using impedance software for prehospital resuscitation quality control and to gain baseline data on prehospital resuscitation practice in the Lothians region of Scotland. Methods: Prospective, observational 3-month pilot study. Broadband modems were placed on ambulance defibrillators and configured on the Lifenet (Physio Control) data network. After a resuscitation attempt the attending EMS crew was asked to telemetry the resuscitation trace to a research computer. The impedance trace was then analysed using computer software (Codestat-Physio Control) and a report on the resuscitation attempt generated. Results: 17 OHCA were included in pilot. All EMS crews agreed to use telemetry. Ten cases met the target of over 70% compression time. Only two cases met the target of a compression rate of 90–110 /min. The defibrillator was used in manual mode in the majority of cases. The mean time from cessation of chest compressions to delivery of defibrillatory shock was 46s. Conclusion: Telemetry of ECG impedance analysis is a straightforward, accurate, accepted method of assessing quality of prehospital resuscitation by ambulance personnel. Baseline data from our region suggests that the quality of advanced life support could be improved by focusing on basic elements of resuscitation. Using software-generated resuscitation reports could be useful for ambulance personnel feedback and monitoring effectiveness of training programmes. Further research is warranted on the widespread use of this technique.